Retrospective evaluation of the utility of two-step surgery for facial basal cell carcinoma and squamous cell carcinoma - Iino, Shiro; Baba, Natsuki; Hasegawa, Takumi; Kasamatsu, Hiroshi; Oyama, Noritaka; Tokunaga, Takahiro; Hasegawa, Minoru (Frontiers in Surgery, 2022)
In older patients with facial basal cell carcinoma (BCC) or squamous cell carcinoma (SCC), surgery should be aimed to reduce treatment-related sequelae and burden with achieving local tumor care. Therefore, we adopted a two-step surgery (TSS) involving the application of a dermal regeneration template onto the skin defect after tumor resection and subsequent reconstruction by full-thickness skin grafting. We performed a detailed comparison of conventional one-step surgery (OSS) and TSS, including evaluation of local tumor curability, postoperative cosmetic and/or functional impairments, and patient burden. Forty-six patients who underwent TSS and 104 patients treated with OSS were retrospectively investigated. The cohort consisted of 77 men and 73 women (median age, 83 years). The BCC: SCC ratio was 56.7%: 43.3%. The tumor size and excision margin were significantly larger in the TSS group than in the OSS group (p = 0.03). The histopathological margin was positive after the first surgery in six cases, but was negative after additional resection in all cases, regardless of OSS or TSS. Local recurrence was not observed in this study. The frequency of postoperative sequelae (POS) in TSS was slightly lower than in OSS (17.4% vs. 27.9%, p = 0.16). A shorter average operation time per session was significantly associated with the location of the vertical defect [below adipose tissue vs. within adipose tissue, estimate: −0.28 (hour), p < 0.001] and surgical procedure [OSS vs. TSS, estimate: −0.13 (hour), p = 0.03] by multiple regression models. The ratio of general anesthesia was relatively lower in TSS than in OSS (9.8% vs. 17.3%, p = 0.12). Thus, TSS showed a good local curability and POS statistically equivalent to OSS, reducing the surgical burden, particularly shortening each operation time without any adverse events, despite the TSS group having significantly larger tumors than the OSS group. Since TSS is a simple procedure, it can be an outstanding option for facial BCC and SCC.